2016
DOI: 10.11113/sh.v8n1-2.836
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Behavior of University Students towards Environmental Issues in Indonesia

Abstract: This paper presents an exploratory study examines environmental knowledge, attitude, behavior and the extent to which they are related among university students in Indonesia. Data collected from students of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
(1 reference statement)
2
8
0
Order By: Relevance
“…Ma'ruf et al surveyed the relationships among environmental knowledge, attitudes and intended behaviour of students at three universities in Padang, Jakarta and Denpasar, Indonesia (Ma'ruf, Surya, & Apriliany 2016). While their results showed that students had good knowledge about the environment, there were only two questions on this in their survey.…”
mentioning
confidence: 99%
“…Ma'ruf et al surveyed the relationships among environmental knowledge, attitudes and intended behaviour of students at three universities in Padang, Jakarta and Denpasar, Indonesia (Ma'ruf, Surya, & Apriliany 2016). While their results showed that students had good knowledge about the environment, there were only two questions on this in their survey.…”
mentioning
confidence: 99%
“…Sharing these ideas are part of GPOCP's routine environmental education and conservation awareness activities. However, attitude is not the only factor that determines whether an individual behaves in an environmentally friendly manner (Ma'ruf et al ., ). We believe that financial concerns are likely a stronger factor in dictating environmental behaviors of our target communities than attitude.…”
Section: Discussionmentioning
confidence: 97%
“…GPOCP's general theory of change (ToC; Dhillon & Vaca, ) underlying our environmental education programs is that as participant knowledge and attitudes about wildlife increase, then they will change their behavior to become more conservation‐friendly (Jacobson, ). A previous study on environmental knowledge and attitudes of university students from Sumatra, Java, and Bali, Indonesia, found that knowledge was a significant predictor of environmental attitudes, and that positive attitudes do contribute to behavior change (Ma'ruf, Surya & Apriliany, ). Some potential examples of behavior change in GPOCP's ToC include the adoption of deforestation‐free livelihoods and the reporting of wildlife crime to law enforcement by participants (and their families, in the case of young students).…”
Section: Discussionmentioning
confidence: 98%
“…(Mamun, Fazal, Ahmad, Yacoob & Mohamad, 2018). Therefore, based on previous studies (Noor, Jamil, Mat, Mat, Kasim, Muhammad & Salleh, 2012;Taufique, Siwar, Chamburi & Sarah, 2015;Kim, Kim & Thapa, 2018;Ma'ruf, Surya & Appriliany, 2016;Zheng, Xu, Kong, Deng & Lin, 2018), there is a positive influence that Objective Knowledge to Environment Attitude. H5: There is a positive relation between Objective Knowledge and Environmental Attitude Relationship between Subjective Knowledge and Product Attitude Hadar, Sood & Fox (2013) obtained that the subjective knowledge of consumer is strongly connected to product related experience.…”
Section: Relationship Between Objective Knowledge and Environmental Attitudementioning
confidence: 92%